FORCED ANALYSIS POCESS OF REED ROLL THREAD FOR SPARK PLUG - Muhammad Yusuf Nurfani (Asosiasi Dosen Muda Indonesia, 2022)
Spark plug is component or device of internal combustion engine (ICE) for make a compression and transfer energy to vehicle. Component of spark plug is center electrode, gasket, hexagon, insulator, corrugation, and terminal nut, the all component will assembly for internal combustion engine component. Thread is a critical component for connection spark plug and engine. the key of perfect thread is reed roll process when the motor makes a shell of part, the forced and rpm should be stable and do not over force for eliminate failure part. This study will discuss of forced analysis on thread and structure analyze from material spark plug after process. The result show in this case useing 2000 rpm and force 197,8N. Based on spot test material after threading, no any crack finding, only black dot due processing. Tortion test after assemblu 5 Kgf, for the lowest sample 1 is 8 Kgf, middle is sample 2 is 12 Kgf, and the bigger is 13 Kgf for sampling test. Igintion on sprak plug are normaly for ignition voltage lower is 13,3 kV, middle 15,3 kV, high 17,5 kV, and average is 15,3kV.